Impact of wind turbine systems on power system voltage stability - Devaraj, D; Jeevajyothi, R (2011 International Conference on Computer, Communication and Electrical Technology, 2011)
This paper investigates the effect of fixed speed and variable speed grid-connected wind generators on the voltage stability of a power system network. The wind generators considered are the squirrel cage induction generator (SCIG), which is a fixed speed, the doubly-fed induction generator (DFIG) and the direct driven synchronous generator (DDSG) which are variable speed. Studies were conducted on a standard five-machine, 14-bus system augmented by a radially connected wind power plant (WPP), which contains 115 wind turbine generators (WTG).The studies include examining the voltage stability (λ-V)curves, voltage magnitude, loading margin and voltage collapse of the system. These voltage stability studies are done for the normal state as well as for line contingencies. It is found that large scale wind power integration at the transmission level has the potential to improve the long-term voltage stability of the grid by injecting reactive power.